2019
DOI: 10.22603/ssrr.2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Results of Percutaneous Endoscopic Transforaminal Lumbar Interbody Fusion: A New Modified Technique for Treating Degenerative Lumbar Spondylolisthesis

Abstract: Introduction Lumbar interbody fusion is used to treat degenerative lumbar spondylolisthesis with instability. We developed a device that safely expands a percutaneous path through Kambin's triangle and used it via a new technique: percutaneous endoscopic transforaminal lumbar interbody fusion (PETLIF). We report in this study the details and outcomes of this procedure after a one year follow-up. Methods Twenty-five patients requiring interbody fusion for degenerative spondylolisthesis of the L4 vertebra were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 31 publications
(25 reference statements)
1
54
0
1
Order By: Relevance
“…As the operation time of endoscope-assisted LIF, a standard approach in our hospital, was 102 (range, 59–162) min [ 24 ], 109.4 min was not significantly different from the operative time for the conventional approach. Likewise, the mean operation time was not inferior to that reported in previous FELIF studies (84.5–285.7 min) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Presently, we only perform FELIF for patients with LDD with disc height loss; the removal of the disc material is not a time-consuming step.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…As the operation time of endoscope-assisted LIF, a standard approach in our hospital, was 102 (range, 59–162) min [ 24 ], 109.4 min was not significantly different from the operative time for the conventional approach. Likewise, the mean operation time was not inferior to that reported in previous FELIF studies (84.5–285.7 min) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Presently, we only perform FELIF for patients with LDD with disc height loss; the removal of the disc material is not a time-consuming step.…”
Section: Discussionsupporting
confidence: 46%
“…Recently, Nagahama et al reported excellent clinical outcomes following transforaminal LIF using a 3.9 mm working channel endoscope (SpineTIP ® Transforaminal Approach Kit, Karl Storz GmbH, Tuttlingen, Germany) [ 17 ]. They treated 25 cases of degenerative spondylolisthesis of the L4 vertebra; the spondylolisthesis was corrected using a PPS system before endoscopic manipulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Although we used standard sheaths in our procedure, they were removed, unlike any of the techniques described above, and retract-sliders that had been inserted beforehand were used for cage insertion (retract-slider group). 8,26 Our previous report 8 was the first to describe this technique. By using a retract-slider, our procedure enables the insertion of a cage larger than a sheath, while protecting the exiting nerve root.…”
Section: Classification and History Of Ppl-lifmentioning
confidence: 99%
“…Although the above-mentioned PPL-LIF could be regarded as a least invasive LIF, it is in the trial and development stage and there are unique techniques for this procedure, which we classified according to the grafting and insertion methods into the intervertebral space (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Among the insertion techniques utilizing the usual sheath (usual sheath [US] group), the insertion technique of comminuted bone and/or other materials without using any cages (without cage subgroup) is the oldest technique, but it has been reported even recently. [9][10][11][12][13] Because of the lack of supporting structure in the intervertebral disk area, which is the main loading part of the lumbar spine, this technique appears to be principally inferior in terms of stability.…”
Section: Classification and History Of Ppl-lifmentioning
confidence: 99%